Dynamic-Interactive Graphics for Statistics (26 Years Later) (2014)
This paper briefly reviews the history of dynamic-interactive graphics for statistics, introduces an example of such graphics, and provides a few glimpses as to the current state of things and the future trends we envision. The general conclusion is that dynamic-interactive graphics for statistics are thriving more than ever as they shift from the desktop to the internet. Thus, dynamic-interactive graphics are becoming increasingly important as they: 1) provide non-experts in statistics with the means to carry out analyses on their own; and 2) teach the basic concepts of statistics to students and practitioners with low to moderate mathematics skills. Their increasing popularity makes the lessons learned over the past 26 years of research on the subject more important than ever.